Human papillomavirus (HPV) vaccination intent and its associated factors: a study of ethnically diverse married women aged 27 to 45 in Malaysia, a Southeast Asian country - Li Ping Wong; Haridah Alias; Farhana Nishat Seheli; Gregory D Zimet; Zhijian Hu; Yulan Lin (Taylor & Francis Group, 2022)
Introduction: This study aimed to investigate HPV vaccination intention among adult married women aged 27 to 45 years and its associated factors, and their spouse/partner's influence on HPV vaccination decision-making. Methods: This is a cross-sectional, questionnaire-based study. Study participants were recruited through simple random sampling of patients attending obstetrics and gynecology outpatient clinics in a university teaching hospital. Participants were selected based on a computer-generated list of a random list of patients attending the clinic. Results: A total of 794 complete responses were received (response rate 88.2%). The mean age of the respondents was 32.2 years with a standard deviation (SD) of ±3.9 years.The vast majority (85.3%) would communicate with their spouse/partner with regard to HPV vaccination decision-making. Nearly 30% (over half were of the Malay ethnic group) perceived their spouse/partner would not consent to their HPV vaccination. Over half (54.9%) reported joint decision-making, and 9.1% (the majority of whom were Malay) reported that HPV vaccination was dependent on their spouse/partner's decision. Intention to vaccinate against HPV was high (74.5%). Factors influencing HPV vaccination intention were spouse/partner's consent to HPV vaccination (odds ratio [OR] = 4.51; 95% confidence interval [CI], 3.08-6.62), being a postgraduate student (OR = 4.55; 95% CI, 2.13-9.72 vs. unemployed/housewife), average household income MYR2000-4000 (OR = 2.09; 95%CI, 1.16-3.78 vs. below MYR2000), and an HPV-related knowledge score of 9-20 (OR = 1.60; 95% CI, 1.10-2.32 vs. score 0-8). Conclusion: Findings highlight the importance of culture-centered interventions to enhance male partner's awareness and support for the HPV vaccination of married women.